2017
DOI: 10.24114/jg.v9i1.6042
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kadar Hara Pupuk Organik Kascing Dari Limbah Kangkung Dan Bayam

Abstract: Pertanian organik merupakan sistem pertanian yang holistik yang mendukung dan mempercepat biodeversiti, siklus biologi dan aktivitas biologi tanah(International Federation of Organic Agriculture Movements,2014). Geografi Pertanian merupakan mata kuliah di Jurusan Pendidikan Geografi FIS Unimed. Dalam Kurikulum Berbasis Kompetensi yang diterapkan di Jurusan Pendidikan Geografi FIS Unimed merupakan matakuliah wajib pada semester genap, tepatnya pada semester IV (empat). Penelitian ini bertujuan untuk mengetahui … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
7
1
1
Order By: Relevance
“…This indicates that vermicomposts from both treatments have alkaline properties, as supported by Azmi et al (2016) that pH value of > 7.5 has alkaline properties. The result of the study was different from the research conducted by Elfayetti et al (2017), who reported that the pH of 3-week old vermicomposts were 6.5 (for water spinach waste feed) and 7.41 (for spinach food waste feed). The difference in the pH value of vermicompost can be due to different feed was given.…”
Section: Results and Discussion Installation Design Of Worm Compostincontrasting
confidence: 99%
See 1 more Smart Citation
“…This indicates that vermicomposts from both treatments have alkaline properties, as supported by Azmi et al (2016) that pH value of > 7.5 has alkaline properties. The result of the study was different from the research conducted by Elfayetti et al (2017), who reported that the pH of 3-week old vermicomposts were 6.5 (for water spinach waste feed) and 7.41 (for spinach food waste feed). The difference in the pH value of vermicompost can be due to different feed was given.…”
Section: Results and Discussion Installation Design Of Worm Compostincontrasting
confidence: 99%
“…The difference in the pH value of vermicompost can be due to different feed was given. The difference in the quality and the amount of feed given to worms can affect the properties and nutrient content of the vermicompost produced (Suim, 1988in Elfayetti et al, 2017. The MC of the 3-week old vermicomposts from the EM4 and molasses treatments was 51.22% and 60.28%, respectively.…”
Section: Results and Discussion Installation Design Of Worm Compostinmentioning
confidence: 99%
“…Vermikompos merupakan salah satu jenis pupuk organik yang dihasilkan dari proses pencernaan dalam tubuh cacing, yaitu berupa kotoran yang telah terfermentasi (Hazra et al 2018). Menurut Elfayetti et al (2012), vermikompos atau kascing adalah campuran kotoran cacing tanah dengan sisa media atau pakan dalam budidaya cacing tanah. Hasil penelitian menunjukan bahwa jumlah produksi vermikompos yang terdekomposisi oleh cacing tanah selama 56 hari pemeliharaan pada empat perlakuan memiliki hasil yang berbeda.…”
Section: Produksi Vermikomposunclassified
“…Plain Water; 3,07 Plain Water;0,91 Plain Water;0,82 Plain Water;3,18 Plain Water;4,09 EM4 65 mL;3,83 EM4 65 mL;2,16 EM4 65…”
Section: Kale Datamentioning
confidence: 99%
“…In this study, the feed used for worms was cow dung, leftover kale, and tomatoes, so that the worm food became more complex. This would produce more complex worm manure minerals as well [3]. There is no doubt that the potency of earthworm manure is that the use of worm manure fertilizer can increase the weight of cultivated plants in the soil, but there has been no research using worm manure in water media in aquaculture cultivation.…”
Section: Introductionmentioning
confidence: 99%